2017
DOI: 10.1111/ctr.12985
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative management after lung transplantation: Results of an international survey

Abstract: Practice patterns in the early postoperative care of lung transplant recipients differ considerably among centers. Many of the reported practices do not conform to consensus guidelines on management of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…11 However, despite the critical role of mechanical ventilation in lung transplantation, very few data are available in the literature to guide clinical practice. 9,12–16 Thus, the currently applied protective mechanical ventilation strategies in lung transplantation patients have been extrapolated from the management of ARDS patients, 17–20 as the benefits of lung-protective mechanical ventilation extend to both patients with ARDS and patients at risk for ARDS. 16…”
Section: Postoperative Management Of Lung Transplantation Recipientsmentioning
confidence: 99%
“…11 However, despite the critical role of mechanical ventilation in lung transplantation, very few data are available in the literature to guide clinical practice. 9,12–16 Thus, the currently applied protective mechanical ventilation strategies in lung transplantation patients have been extrapolated from the management of ARDS patients, 17–20 as the benefits of lung-protective mechanical ventilation extend to both patients with ARDS and patients at risk for ARDS. 16…”
Section: Postoperative Management Of Lung Transplantation Recipientsmentioning
confidence: 99%
“…The goals of MV following lung transplantation are to promote graft function, maintain adequate gas exchange, and prevent ventilator-induced lung injury [ 7 ]. There have been no large, multicenter trials to guide MV management after lung transplantation despite the critical role of MV in lung transplantation, and only a few studies have addressed appropriate MV after lung transplantation [ 22 , 23 ]. Despite wide variation in practice, the currently applied lung protective MV strategies in lung transplantation have been extrapolated from the practice guideline for MV patients with acute respiratory distress syndrome (ARDS), since experimental data suggest that all lung transplantation recipients are at risk of ventilator-induced lung injury [ 24 ].…”
Section: Management Of Mechanical Ventilationmentioning
confidence: 99%
“…Therefore, individualized management is required to maintain adequate perfusion pressure balance with the lowest possible cardiac output to reduce the exacerbation of pulmonary edema risk. Postoperative volume status management is actually an area of considerable heterogeneity in practice [ 23 ]. The implementation of a dedicated protocol that maintains specific hemodynamic targets has been shown to be associated with reduced graft dysfunction severity [ 46 ].…”
Section: Management Of Hemodynamicsmentioning
confidence: 99%
“…According to a recent multicenter survey, more than half of respondents answered that propofol in combination with opiates were preferred over other combinations, such as opiates with intermittent benzodiazepine. However, approximately 40% reported that there is no official drug policy on sedation and analgesia for the transplanted patient [38]. Recently, the use of dexmedetomidine, a selective alpha agonist, has been increasing in ICUs.…”
Section: Immediate Postoperative Management Of Lung Transplantationmentioning
confidence: 99%